THE EVALUATION OF PEDESTRIAN FACILITIES IN UNIVERSITAS PANCASILA AREA - Nuryani Tinumbia; Wita Meutia; Gunawan Suryaatmaja (Jurnal Infrastruktur, 2022)
The campus area has a potential to generate pedestrian trips for relatively close trips such as access between buildings or faculties. Then the provision of adequate pedestrian facilities in this area is important, moreover this is also one of the indicators in the UI Green Metric assessment. This study aims to determine the existing condition of pedestrian facilities in Universitas Pancasila educational area through an assessment developed by ADB with nine walkability parameters, to determine the perceptions of pedestrians on the quality of the facilities and to provide recommendations based on research results for improving the quality of pedestrian facilities in the campus area. The survey was conducted by distributing online questionnaires and an inventory survey of pedestrian facilities. The result indicates the presence of pedestrian facilities is sufficient, although some improvements are needed in several paths. The proposed improvement recommendations are improving disability facilities and pedestrian paths (the availability and its maintenance), adding crossing facilities and removing barriers on paths.